O035 Elevated liver enzymes in paediatric sleep disordered breathing. (9th November 2022) - Noone, A; Lao, Y; Crawford, T; Kennedy, D; Martin, J; Ferrante, A; Wabnitz, D; Kontos, A
Abstract: Introduction: Paediatric sleep disordered breathing (SDB) is associated with adverse cardiovascular outcomes. Non-alcoholic fatty liver disease (NAFLD) and dyslipidaemia are potential modifiable risk factors for cardiovascular disease, often coexisting in adults with SDB. Increases in lipid outputs from the liver have been identified in obese adults and children with SDB. Whether children with SDB compared to healthy non-snoring controls have evidence of elevated serum lipids and associated liver enzyme changes were assessed. Methods: Seventy-five children (SDB=49, controls=26) between the ages of 6-17 years matched for age, gender and BMI underwent overnight polysomnography to measure SDB severity and provided a fasting blood sample to assess lipid and liver panels. Results: OAHI was significantly increased in children with SDB compared to healthy non-snoring controls (p < 0.05). Serum potassium, alanine aminotransferase and lactate dehydrogenase were significantly increased in children with SDB, while albumin was significantly decreased (p < 0.05). No differences were found between serum lipid levels. Conclusion: The presence of paediatric SDB may increase the risk of developing NAFLD. Further investigation is required to determine whether routine assessment of liver enzymes should be implemented in paediatric SDB. Whether surgical removal of the adenoids and tonsils to treat paediatric SDB can stabilise liver enzyme levels requires further research.